Meningkatkan Kompetensi Interpreting dengan Menerapkan Metode Skenario Role-Play and Simulation - Mobit, Mobit; Risatyah, Anisa (Majalah Ilmiah SOLUSI, 2015)
Interpreting is one of the language skills which is necessary for the global communication. The required competency shoud be owned by the students (interpreters) is how to translate orally of a source language to the target language well. To create the competent interpreters, an institution should find the best teaching strategy and techniq out. This research used qualitative approach and classroom action research in which deals with some investigations which adress to improve the ongoing technique used and get the better teaching technique variation of Role-play and Simulation scenario in teaching of Interpreting.. The result of the reserach indicates that the second cycle of two implemented cycles was the convinient techniq to the participants. Key words: interpreter, translate, teaching, techni, role-play, simulation